2020
DOI: 10.1111/tbed.13650
|View full text |Cite
|
Sign up to set email alerts
|

Stability of African swine fever virus on heat‐treated field crops

Abstract: African swine fever (ASF) is an infectious disease of domestic pigs and wild boar that causes a haemorrhagic fever-like illness with exceptionally high lethality (Penrith & Vosloo, 2009). The causative agent is a large enveloped DNA virus of the Asfarviridae family, genus Asfivirus. Its large genome, with a size between 170 and 190 kbp-depending on the strain, encodes more than

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 20 publications
2
46
1
1
Order By: Relevance
“…To detect infectious virus, samples were tested using the haemadsorption test (HAT) as published previously [ 37 ]. When cytotoxicity of samples was observed, these were prediluted 10-fold in medium and tested again.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect infectious virus, samples were tested using the haemadsorption test (HAT) as published previously [ 37 ]. When cytotoxicity of samples was observed, these were prediluted 10-fold in medium and tested again.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study estimated that the half-life of infectious ASFV ranges from 0.65 days in faeces stored at 4 °C to 0.29 days in faeces stored at 37 °C, and from 2.19 days in urine stored at 4 °C to 0.41 days in urine stored at 37 °C [ 36 ]. Regarding contaminated field crops, the probability of ASFV transmission has been estimated as low, if crops are stored in a dry place at room temperature for at least two hours [ 37 ]. ASFV is resistant to changes in pH, and certain strains have been reported to be resistant to complete inactivation at pH values between 4 and 13 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study [5] conducted on ASF in Latvia suggested that fresh grass or crops contaminated by wild boars and used as feed had been a risk factor for ASF occurrence in backyard holdings. In their recent study, Fischer et al [54] took six different types of ASF-contaminated field crops (wheat, barley, rye, triticale, corn, and peas) and tested the efficacy of drying and heat treatment towards the inactivation of ASFV. They analysed samples for the presence of viral DNA and infectious virus after drying at room temperature or at moderate temperature (between 40 • C and 75 • C).…”
Section: Human Activity Factors and Farm Managementmentioning
confidence: 99%
“…Furthermore, the manufacturing process of SDPP in US and EU includes the step of storage of the final packed spray-dried product at 20°C for 14 days [ 4 ]. Recently Fischer et al [ 38 ], demonstrated that ASFV inoculated on SDPP and stored at room temperature (20°C) for 14 days was inactivated by more than 5 logs. The combination of these various process control steps reduces the risk of ASFV transmission through SDPP to essentially zero, as already recognized by ANSES [ 37 ].…”
Section: Discussionmentioning
confidence: 99%